ADA / ABA handbook : accessibility guidelines for buildings and facilities (Building News Inc., 2004)
This book contains the full text of the new (July 2004) ADA and ABA guidelines, organized and presented in an easy-to-use format with an extended index and enhanced illustrations. What's more, you'll find all similar subjects contained in the same chapter, with cross-references to all relevant guidelines, and special advisories to enhance your understanding of the guidelines and their practical application. If you've ever had a question on accessibility guidelines, or what is required in designing or building to within the ABA and ADA guidelines, you should have the ADA & ABA HANDBOOK close by. --